2016
DOI: 10.1590/0034-7167.2016690223i
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados a acidentes de trânsito com mototaxistas

Abstract: RESUMO Objetivo: identificar a prevalência de acidentes motociclísticos envolvendo mototaxistas e fatores associados. Método: estudo transversal e exploratório, com aplicação de questionários aos mototaxistas das 32 praças de Caicó, Rio Grande do Norte, Brasil (N=420). Resultados: os mototaxistas têm alta carga horária de trabalho diária (12 horas em média) e foi verificado que 63,6% já se envolveram em pelo menos um acidente motociclístico. A ocorrência de acidentes motociclísticos foi associada significat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
0
5
0
20
Order By: Relevance
“…Previous literature concluded that there is relationship between individual’s activities and road accidents; motorcyclists and taxi drivers are more accident-prone due to their longer rush hour involvement. He has also postulated specific education to prevent accidents and certain service concerning accidents and emergency measures to soften the consequences ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature concluded that there is relationship between individual’s activities and road accidents; motorcyclists and taxi drivers are more accident-prone due to their longer rush hour involvement. He has also postulated specific education to prevent accidents and certain service concerning accidents and emergency measures to soften the consequences ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Verificou-se que 52,8% possuíam ensino médio completo e apenas um tinha ensino superior, sugerindo a baixa escolaridade da categoria 6 . Em outro estudo, a ocorrência de acidentes moto ciclísticos foi associada significativamente com escolaridade 14 . Em um estudo foi constatado que 82,9% dos acidentes ocorreram durante o trabalho.…”
Section: Discussionunclassified
“…Unfortunately, the use of PPE by the driver is still neglected even though it is mandatory, which favours the high rate of injuries in Brazil [1]. The literature reports that 60.2% of motorcyclists did not wear a helmet, contrary to one study in Thailand, where 65.0% reported using it [24].…”
Section: Discussionmentioning
confidence: 99%